Electrochemical and quantum chemical study of albendazole as corrosion inhibitor for mild steel in hydrochloric acid solution - Ahamad I.; Prasad R.; Ebenso E.E.; Quraishi M.A. (My University, 2025)
Inhibition effect of Albendazole on the mild steel corrosion in molar hydrochloric acid was investigated using weight loss, electrochemical impedance spectroscopy (EIS) and polarization techniques. The results show that Albendazole is an effective inhibitor for mild steel corrosion in 1 M HCl solutions and inhibition efficiency is >90% at inhibitor concentration of 0.4 mM. Adsorption of the inhibitor on the mild steel surface followed Langmuir adsorption isotherm. The value of free energy of adsorption (ΔG°ads) indicated that adsorption of Albendazole molecule is a spontaneous process and it adsorbs chemically as well as physically. Polarization studies showed that albendazole is a mixed-type inhibitor. Quantum chemical calculations were performed on Albendazole using unrestricted Kohn-Sham formalism at density functional theory (DFT) level based on self-consistent field (SCF) method with the 6-31**G (d,p) basis set for all atoms by Gaussian 03W program. The different quantum chemical properties were calculated and discussed. © 2012 by ESG.